Teaching reading : a balanced approach for today's classrooms - Farris, Pamela J.; Fuhler, Carol J.; Walther, Maria P. (Boston, Mass. : McGraw-Hill, 2004)
Provides a practical, research-based introduction to teaching elementary-aged children to read. This text shows teachers how to use a variety of strategies to meet individual student needs. Built on a research base containing the modern findings and theories in literacy instruction, it shows pre-service teachers how to put theory into practice
Includes bibliographical references and index.
Keywords: Reading; Language arts